Effects of sleep deprivation on healthy adults: a systematic review (Research, Society and Development, 2021)
Currently, due to the contemporary lifestyle, individuals have shown a reduction in the number of hours of daily sleep, this generates physiological, psychological, behavioral, and abiding in the health of the population. Our main objective was to investigate these consequences on the health of healthy individuals. A systematic review was performed in databases following the PRISMA protocol and the guidelines of the Chrocraine Handbook. We selected 27 articles that served as the basis for this study, in the following axes: endocrinology, performance, neuroscience and physiological changes. Given the various harmful effects found, more studies within these areas should be conducted, with deeper analysis of the effects of sleep deprivation on the health of healthy adults.